Oppozitsiia . Oppozitsiia . Opposition . Оппозиция - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interviews with deputies on democratization and privatization and their comments on the ongoing economic reforms. Featured in the program: Chelnokov, Mikhail Borisovich (People's Deputy) Contributors: Pankov, Vladimir (Anchor) Интервью с депутатами о демократизации и приватизации и их комментарии о проводимых экономических реформах. В программе участвуют: Челноков, Михаил Борисович (Народный депутат) Создатели: Панков, Владимир (Ведущий/Ведущая)